2015
DOI: 10.1016/j.molcel.2015.10.013
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Activation Requires Local Unfolding of an Autoinhibitory Domain

Abstract: SUMMARY Poly(ADP-ribose) polymerase-1 (PARP-1) creates the posttranslational modification PAR from substrate NAD+ to regulate multiple cellular processes. DNA breaks sharply elevate PARP-1 catalytic activity to mount a cell survival repair response, whereas persistent PARP-1 hyperactivation during severe genotoxic stress is associated with cell death. The mechanism for tight control of the robust catalytic potential of PARP-1 remains unclear. By monitoring PARP-1 dynamics using hydrogen/deuterium exchange-mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
324
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(349 citation statements)
references
References 59 publications
25
324
0
Order By: Relevance
“…As PARP-1 participates in DNA damage repair, the single application of a PARP-1 inhibitor treatment or a DNA damage drug combination may promote apoptosis (21). A previous study has demonstrated that drug inhibition or gene knockout PARP-1 may not only cause the avoidance of tissue damage caused by oxidative stress, but may also improve the prognosis of patients with cancer (22). Additionally, in the present study, HCPT effectively activated the PARP-1 protein expression of human osteosarcoma MG-63 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As PARP-1 participates in DNA damage repair, the single application of a PARP-1 inhibitor treatment or a DNA damage drug combination may promote apoptosis (21). A previous study has demonstrated that drug inhibition or gene knockout PARP-1 may not only cause the avoidance of tissue damage caused by oxidative stress, but may also improve the prognosis of patients with cancer (22). Additionally, in the present study, HCPT effectively activated the PARP-1 protein expression of human osteosarcoma MG-63 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upon association of PARP-1 with a break site, these protein domains are refolded to promote extensive interdomain contacts that facilitate PARP-1 catalytic activity (Langelier et al 2012). Moreover, DNA binding induces unfolding of an autoinhibitory helical domain (HD), which then allows for NAD + binding and activation of PARP-1 (Dawicki-McKenna et al 2015;Steffen et al 2016). The recognition of single-stranded breaks by Zn1 and Zn2 promotes the folding of other PARP-1 domains and subsequent allosteric activation (Eustermann et al 2015).…”
Section: Structural Analyses Of Parps In Dna Repairmentioning
confidence: 99%
“…PARP1 is a multi-domain protein composed of six distinct modules including two N-terminal zinc finger domains (Zn1 and Zn2) responsible for initial binding to altered DNA structures; the third zinc-binding domain (Zn3) and tryptophan-glycine-arginine (WGR) domain participating in DNA binding and formation of a network of interdomain contacts critical for activation of the C-terminal catalytic (CAT) domain resulting in NAD + cleavage and formation of PAR polymer; and a central auto-modification domain containing a cluster of glutamic acid residues serving as ADP-ribose acceptor sites: a BRCA1 C-terminal (BRCT) motif (1618). Both PARP1 and PARP2 have WGR and CAT domains and the overall three-dimensional structures of theirs CAT domains are similar (19).…”
Section: Introductionmentioning
confidence: 99%